Synergistic activity of a short lipidated antimicrobial peptide (lipoAMP) and colistin or tobramycin against Pseudomonas aeruginosa from cystic fibrosis patients12. Issue 1 (20th October 2015) - de Gier, Martin G.; Bauke Albada, H.; Josten, Michaele; Willems, Rob; Leavis, Helen; van Mansveld, Rosa; Paganelli, Fernanda L.; Dekker, Bertie; Lammers, Jan-Willem J.; Sahl, Hans-Georg; Metzler-Nolte, Nils
Abstract : Synergistic effects between a lipoAMP and colistin against clinical P. aeruginosa strains isolated from cystic fibrosis patients are described. Abstract : Declining pulmonary function, ultimately culminating in respiratory failure, is mainly caused by chronic Pseudomonas aeruginosa ( P. aeruginosa ) infections in patients with cystic fibrosis (CF). Due to its hypermutability, allowing rapid adaptation to the selective constraints in a lung with CF, and the ability to form biofilms, P. aeruginosa is able to colonize and damage the lung by chronic infection. Exacerbations are being treated with a combination of common anti-pseudomonal antibiotics, but (pan)resistance is increasingly reported. Antimicrobial peptides (AMPs) have a broad spectrum of antibacterial activity, and their effectiveness is, still, less affected by induction of resistance. Here, we explore the in vitro applicability of a RWRWRWK(C10 ) synthetic lipoAMP (named BA250-C10), a lipidated peptide with a C10 -lipid chain attached to the C-terminus, as a novel antibacterial agent against P. aeruginosa ; and in particular, its ability to inhibit biofilm formation. BA250-C10 was tested for its in vitro antibacterial activity against 20 clinical P. aeruginosa isolates from CF patients, each having a different resistance profile and ability to form biofilms. The modest antibacterial activity of the peptide against most P. aeruginosa strains (16–256 μg mL −1 ) was significantly increased in the presence of colistin or tobramycin, supported by the results from the checkerboard assay and growth curves. In three biofilm-forming strains, a synergistic effect was observed for BA250-C10 with colistin, but less with tobramycin. This indicates that combinations of lipidated AMPs and colistin may be further pursued as a potential novel treatment strategy against P. aeruginosa infections in CF patients.